Analisis Kebutuhan Optimalisasi Pembelajaran Menyeluruh Berbasis Bilingual dalam Mewujudkan Pembelajaran Berkualitas Bagi Peserta Didik - Fitrianti, Novia; Kavina, Hufadz Nadiyya; Wulandari, Nevita; Sarumaha, Putri Anita; Ummah, Yazila Roofiqotul; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses the importance of optimizing bilingual learning in realizing quality education in the era of globalization. Bilingual learning, which combines Indonesian and a foreign language (especially English), aims to improve linguistic intelligence, communication skills, and prepare students to face global challenges. The research method used is a literature study by collecting and analyzing data from various sources such as books, journals, and previous research related to bilingual learning in elementary schools. The literature study in this article shows that the success of bilingual learning is highly dependent on teacher resources, equipment, teacher and student readiness, and facilities and infrastructure needed in the learning process and is a crucial factor in creating an effective learning environment. Thus, optimizing bilingual learning requires a holistic approach that includes careful planning, teacher resources, equipment, teacher and student readiness, and facilities and infrastructure to achieve quality and relevant education goals in the global era.